Space Between Her Lips : The Poetry of Margaret Christakos - Hill, Gabrielle L'Hirondelle, 1979-; Reder, Deanna, 1963-; Gaertner, David, 1979-; McCall, Sophie, 1969- (Book collections on Project MUSE., 2017)
"The goal of Read, Listen, Tell is not only to share with readers an incredibly diverse collection of Indigenous stories, but also to transform methods of reading by bringing into the forefront practices in interpreting texts that are grounded in Indigenous knowledge and scholarship. Each of the chapters offers particular strategies for reading the stories in multiple ways, encouraging readers to expand the scope of the "short story" by including a broad range of story forms. The chapters consist of five to seven stories, accompanied by a critical essay that helps contextualize some of the questions and issues the stories raise."--